Management of Ship Waste in A Seaport as An Element of Environmental Management on The Example of The Port of Gdynia - Sławomir SKIBA (Communications of International Proceedings, 2023)
The development of the transportation system taking into account ecological aspects in the literature is generally defined as the shaping of a sustainable transportation system. Thus, the shaping of a sustainable transport system is related not only to the implementation of transport policy objectives, but also to environmental issues such as air, land and water pollution, noise, or vibrations emitted by means of transport. Environmental management issues do not bypass seaports. The purpose of this article is to identify the basic principles of waste management in a seaport, using the port of Gdynia as an example. The article is of a review nature with the elements of case study. The following methods were used: narrative literature review, synthesis, and methods of logical reasoning (deduction, induction, and abduction). This study contributes to the literature by providing new theoretical explanations for the relationship between management of ship waste in a seaport and environmental management.
Keywords: Maritime transport; waste management; environmental protection